Disseminated skeletal muscle and cardiac metastasis from squamous cell carcinoma of the lung detected with FDG and FLT PET/CT - Tarun Jain; Sampanna Rayamajhi; Rajender Basher; Dheeraj Gupta; Venkata Maturu; Bhagwant Mittal (World Journal of Nuclear Medicine)
Lung cancer is one of the leading cancers all over the world. Positron emission tomography (PET) using 18F fluorodeoxyglucose (18F FDG) is useful for staging of the disease and decide the appropriate management. 3Ͳ-deoxy-3Ͳ-18 F-fluorothymidine (18F FLT) is a tracer being extensively evaluated currently and is said to represent tumor proliferation. Common sites of metastases from lung cancer include adrenal glands, bone, and brain. Muscle metastasis and cardiac metastasis are uncommon findings. We report a case of squamous cell carcinoma of the lung with metastases to multiple skeletal muscles and myocardium detected with both FDG and FLT PET/computed tomography (CT).